Resubmission of quantity details of first batch for prefabricated steel structure of BRAC University new campus project - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding resubmission of quantity details of first batch for prefabricated steel structure of BRAC University new campus project.